Janusz Mariański, Religious Practices in Poland in the Process of Transformation. The Sociologi- cal Study, Wydawnictwo Diecezjalne i Drukarnia w Sandomierzu, Sandomierz 2014, pp. 392. - Kozak, Jarosław (Horyzonty Wychowania, 2015)
Recenzja